Communication—Porous Activated Carbon from Amorphophallus Konjac by One Step Method for High Performance Supercapacitors. Issue 4 (26th February 2019) - Wan, Hengcheng; Li, Qi; Ge, Huilin; Qu, Zhiying; Zhu, Wenkun; Duan, Tao
Abstract : Porous activated carbons (AC) have been synthesized from natural biomass material amorphophallus konjac powder by one-step method to make a carbonization and activation with potassium hydroxide. The three-electrode system tests show that the porous structure KGAC-X samples have excellent electrochemical performance, especially the KGAC-2 electrode showing superior specific capacitance (169.8 F g −1, current density 1 A g −1 ) and excellent rate performance (212.5 F g −1, current density 1 A g −1 ) in the 1 M KOH electrolyte. This study provides a facile, economical, and effective route to prepare commercial activated carbon electrode material with high porosity for supercapacitors.